The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1179/174313208x353712
|View full text |Cite
|
Sign up to set email alerts
|

Topographical and quantitative distribution of the projecting neurons to main divisions of the septal area

Abstract: Afferents from the interanterodorsal and mediodorsal thalamic nuclei, which increase the role of the septal area in arousal and awareness, are reported for the first time. Projecting cells to the MS support the learning-related function of this area. Projecting cells to the LS that are more scattered throughout the brain indicate its involvement in more diverse functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…No collaterals were observed either in the medial thalamus or in the habenular complex from any accumbal region (Nauta et al,1978), consistent with posterior studies using more sensitive tracers (Heimer et al,1991; Usuda et al,1998). Scant projections to the lateral septum obtained only after injections in the medialmost AcbSh (Heimer et al,1991) were not observed either, consistent with other anterograde or retrograde labeling studies (Swanson and Cowan,1979; Risold and Swanson,1997; Usuda et al,1998; Haghdoost‐Yazdi et al,2009). Minor projections to the bed nucleus of the stria terminalis (BST) have been reported from the dorsomedial AcbSh (Heimer et al,1991; Usuda et al,1998), which may have been missed in our single dorsomedial AcbSh injection that spared most of the dorsomedial cone; however, a retrograde labeling study injecting in BST did not find any labeled neurons in the ventral striatum (Weller and Smith,1982).…”
Section: Discussionsupporting
confidence: 80%
“…No collaterals were observed either in the medial thalamus or in the habenular complex from any accumbal region (Nauta et al,1978), consistent with posterior studies using more sensitive tracers (Heimer et al,1991; Usuda et al,1998). Scant projections to the lateral septum obtained only after injections in the medialmost AcbSh (Heimer et al,1991) were not observed either, consistent with other anterograde or retrograde labeling studies (Swanson and Cowan,1979; Risold and Swanson,1997; Usuda et al,1998; Haghdoost‐Yazdi et al,2009). Minor projections to the bed nucleus of the stria terminalis (BST) have been reported from the dorsomedial AcbSh (Heimer et al,1991; Usuda et al,1998), which may have been missed in our single dorsomedial AcbSh injection that spared most of the dorsomedial cone; however, a retrograde labeling study injecting in BST did not find any labeled neurons in the ventral striatum (Weller and Smith,1982).…”
Section: Discussionsupporting
confidence: 80%
“…The fast AHP probably minimizes the refractory period by promoting Na + channel de-inactivation and limiting the activation of slow voltage-gated K + currents. Moreover, in Drosophila MNs (present study) and in cerebellar Purkinje neurones (Haghdoost-Yazdi et al 2008), BK current is required for spike shape and spike frequency control only in bursting mode but not during tonic firing. Here, BK channel properties appear to be tuned so that (i) full activation occurs only during strong and prolonged depolarizations with coincident Ca 2+ influx such as in burst mode; (ii) activation is sufficiently fast to occur within the duration of a single Na + spike within bursts; and (iii) inactivation is sufficiently fast so that BK outward current does not oppose the next spike of the burst.…”
Section: Cf Keeps Mn Postsynaptic Depolarizations In Response To Cpmentioning
confidence: 65%
“…There is considerable overlap in noradrenergic innervation to the brain regions that were studied here. The MPA appears to receive noradrenergic innervations from the A2 and A6 noradrenergic nuclei [44], while the DBB receives innervation from A6 [45] and the OVLT from A1 [46]. The PVN receives noradrenergic input from the A1 and A2 regions [47], the BNST from A1 [46] and the CeA from A2 region [48].…”
Section: Discussionmentioning
confidence: 99%